Incidence and Outcomes of Acute Renal Failure Following Liver Transplantation: A Population-Based Cohort Study. Issue 52 (December 2015) - Chen, Hsiu-Pin; Tsai, Yung-Fong; Lin, Jr-Rung; Liu, Fu-Chao; Yu, Huang-Ping
Abstract : Abstract: The aim of our large, population-based, cohort study was to explore the risk factors of acute renal failure (ARF) after liver transplant (LT) in Taiwan. From the Taiwanese National Health Insurance Research Database, 2862 patients who had undergone LT without pretransplant dialysis between July 1, 1998, and December 31, 2012, were identified. Preoperative, operative, and perioperative risks factors were considered and analyzed using logistic regression analysis, after adjusting for age and sex. All patients were followed up until the study endpoint or death. The final dataset included 214 patients with ARF and 2648 without ARF post-LT. Preoperative cerebrovascular diseases were the most important identifiable risk factor for ARF post-LT. Comparison of outcomes for patients "with" and "without" ARF indicated higher incidence rates of bacteremia, pneumonia, and postoperative bleeding, as well as longer stays in both intensive care unit and hospital. Kaplan–Meier mortality curves identified higher rates of mortality for patients' developing ARF at 1-year post-LT and overall at 14.5 years postsurgery. We provide evidence of a high incidence of ARF post-LT in Taiwan, with documented association of ARF with higher incidence rates of morbidity and mortality in this clinical population. The most important identifiable risk factor for ARF in our study was cerebrovascular diseases.